Influence of regular practice of various sports on harmonicity of physical development of the of young athletes of Uzbekistan - R. Kamilova; L. Isakova; M. Zilola; O. Kim (Спортивная медицина: наука и практика, 2020)
One of the integrated indicators of a harmony of physical development of an organism is the body mass index, which allows to estimate a relationship of the body weight to its the body height. Objective: to evaluate an influence of regular practice of various sports on harmonicity of physical development of the of young athletes of Uzbekistan. Materials and methods: 13849 athletes aged from 11 to 17 years (9973 boys and 3876 girls) residents of Tashkent, Nukus, Samarkand, Gulistan, Karshi and Urgench were examined. Depending on the sport and the period of the training sessions, the subjects were divided into 3 groups: children with training period up to 1 year (1 group - control group), children engaged in sports for 1-2 years (group 2) and children engaged in sports for 3 and more years (3rd group). Somatometric and calculation methods were used. Results: normal values of body mass index in female and male enlarged with training irrespective of sport. Youth athletes engaged in sport 3 and more years were characterized by a normal ratio of growth and body weight. Normal body mass index in study groups were found more often than in the control group. Conclusions: it is necessary to carry out a timely assessment of physical development in youth for implementation of individual approach to choice of sport and determination of optimum value of physical activity.